Penerapan Konsep Tradisi “Baayun Mulud” sebagai Inspirasi Busana Pesta Malam - Nisa, Khairun; Suprihatin, Sri Emy Yuli (Fashion and Fashion Education Journal, 2024)
Clothing is something that is closely related to humans today. Various types and forms of clothing are created to meet the trends and needs of society, one type of clothing that is growing the most is evening party clothing. This clothing has changed from year to year so that designers are required to be more creative and innovative in creating tonight's party clothing. The innovation that can be offered is by applying concepts that exist in Indonesian traditions as a source of inspiration in developing clothing. One tradition that can be a source of inspiration and concept in developing evening party clothing is the "baayun mulud" tradition in South Kalimantan. This research aims to find out to what extent the tradition chosen by the author can be used as a concept and source of inspiration in developing evening party clothing. The method used in this research is quantitative research using an experimental approach where the author carries out his own experiments in making his clothes directly. The results of this research show that several components in the "baayun mulud" tradition can be applied in the development of evening party clothing, whether represented in form or other things.